THE INFLUENCE OF PERCEPTIONS OF TRUST AND PERCEPTIONS OF SECURITY ON THE EFFICIENCY OF USING QRIS AS A MEANS OF DIGITAL PAYMENT FOR KARANGANYAR REGENCY MSMEs - Evi Mutma’inah; Estina Vitasari; Erlita Annastasya (CV. Adiba Aisha Amira, 2026)
The increasing use of digital payment systems has encouraged MSMEs to adopt QRIS as a cashless payment method. This study aims to examine the effect of perceived trust and perceived security on the efficiency of QRIS usage among MSMEs in Karanganyar Regency. This research uses a quantitative approach with primary data collected from 108 MSMEs through questionnaires. Data analysis was conducted using multiple linear regression with SPSS. The results show that perceived trust does not significantly affect QRIS usage efficiency, while perceived security has a positive and significant effect. However, perceived trust and perceived security simultaneously have a significant effect on QRIS usage efficiency. The coefficient of determination indicates that 34.9% of the variation in efficiency is explained by the two variables. This study concludes that security perception plays a more important role than trust in improving QRIS usage efficiency among MSMEs